Energy budget of Jatropha-based cropping systems in Tarai area of Central Himalayas, India - RASTOGI, AKANKSHA; SINGH, VIR (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was carried out to work out energy budget of Jatropha curcas L. sown exclusively and intercropped with three food crops, viz. wheat, mustard and soybean, in Pantnagar University farm at Tarai area of Himalayan foothills during crop season 2017. The results showed that the energy use efficiency expressed as the outputinput energy ratio, was highest in case of wheat cultivated as a sole crop (6.76). When the wheat was intercropped with Jatropha, the output-input ratio declined to 4.20. Energy productivity (per ha basis) figures brought to the fore the fact that on investing one kJ the highest production was in case of wheat cultivated as a sole crop (18. 88×10-5 kg/kJ). The value decreased to 11. 74×10-5 kg/kJ in the Jatropha-wheat intercropping system. A trend of decrease in energy productivity of food crops in the Jatropha-based intercropping system revealed that these cropping systems were not favourable for harvesting more energy of useful production. Jatropha’s own energy productivity (12. 40×10-5 kg/kJ) was comparatively lower than all the food crops raised as sole crops but relatively higher when the crops were raised with Jatropha. The figures of specific energy increased with the cultivation practice of Jatropha-based intercropping of food crops. The net energy values for wheat raised under both the systems surpassed the values for Jatropha and all other food crops. In case of each food crop, the values of net energy decreased on cultivation of the crop with Jatropha. We can arrive at the conclusion that the Jatropha-based intercropping is not a promising agronomic practice.